Things versus People: Gender Differences in Vocational Interests and in Occupational Preferences - Andreas Kuhn; Stefan C. Wolter (Institute of Labor Economics (IZA), 2020)
Occupational choices remain strongly segregated by gender, for reasons not yet fully understood. In this paper, we use detailed information on the cognitive requirements in 130 distinct learnable occupations in the Swiss apprenticeship system to describe the broad job content in these occupations along the things-versus-people dimension. We first show that our occupational classification along this dimension closely aligns with actual job tasks, taken from an independent data source on employers' job advertisements. We then document that female apprentices tend to choose occupations that are oriented towards working with people, while male apprentices tend to favor occupations that involve working with things. In fact, our analysis suggests that this variable is by any statistical measure among the most important proximate predictors of occupational gender segregation. In a further step, we replicate this finding using individual-level data on both occupational aspirations and actual occupational choices for a sample of adolescents at the start of 8th grade and the end of 9th grade, respectively. Using these additional data, we finally also show that the gender difference in occupational preferences is largely independent of individual, parental, and regional controls.
Keywords: J16; J24; D91; 330; gender differences; occupational choice; occupational segregation; things versus people; preferences; job content